Oil Money : Middle East Petrodollars and the Transformation of US Empire, 1967-1988 - Wight, David M., 1985- (Book collections on Project MUSE., 2021)
"History of how international petrodollar flows transformed the role of the Middle East within the global empire of the United States during the 1970s and 1980s, both increasing Middle East-US cooperation and generating cultural and political backlashes, with particular focus on US relations with Egypt, Iran, Iraq, and Saudi Arabia"--